Coimbra as a literary tourism destination: landscapes of literature - Quinteiro, Sílvia (2020)
Literary tourism is commonly recognised as a part of cultural tourism (Baleiro and Quinteiro, 2018; Hoppen, 2011; Magadán Díaz and Rivas García, 2011, Richards, 1996, Robinson and Andersen, 2002) or of heritage tourism (Squire, 1996; Herbert, 2001). Butler (2000: 360) has defined literary tourism as “the form of tourism in which the primary motivation for visiting specific locations is related to interest in literature”. Along the same lines, literary tourism has been defined as the practice of visiting places associated with writers and their texts (Watson, 2009) and as a form of tourism which is “associated with places celebrated for literary depictions and/or connections with literary figures” (Squire, 1996: 119). That is, practicing literary tourism means travelling to the places of literature, i.e. the “literary places” (Herbert, 2001) associated with authors’ biographies and their works.